Role of Steroid Therapy in Pseudoxanthoma Elasticum-like Papillary Dermal Elastolysis. (October 2013) - Pranteda, G.; Muscianese, M.; Marmo, G.; Fidanza, L.; Pranteda, G.; Tamburi, F.; Bottoni, U.; Nisticò, S.
Pseudoxanthoma Elasticum -like Papillary Dermal Elastolysis (PXE-PDE) is a peculiar idiopathic elastolytic disorder that clinically resembles Psudoxanthoma elasticum (PXE). It is histologically characterized by a total or partial loss of elastic fibers in the papillary dermis. It more often affects elderly women and is characterized by asymptomatic and symmetrical yellowish papules localized predominantly on the neck, supraclavicular regions, and flexural areas. After analyzing a series of cases and the recent literature suggesting that glucocorticoids may down-regulate the elastin gene expression and elastin mRNA, in cultured human skin fibroblasts, we think that high dose and prolonged steroid therapy may contribute to the appearance of PXE-PDE lesions.